Smart shirt and carpet for annotating child behaviour in autism research - Nadeem, Ali; Palovuori, Karri; Kylliäinen, Anneli; Helminen, Terhi; Virkki, Johanna (Finnish Journal of eHealth and eWelfare, 2023)
This study presents a developmental solution for annotating events, eye-contact, in live interaction scenarios, such as autism research. The approach involves prototyping infrared light emitting diodes (IR LEDs) integrated into both a smart shirt and smart carpets. Leveraging the imperceptibility of IR LEDs to the human eye ensures minimal disturbance to the individuals under surveillance. During video analysis, researchers can identify instances of eye-contact through the activation of IR LEDs, aiding in the recognition of corresponding events. The prototyped smart shirt features a necklace-type design with embedded IR LEDs, while two distinct designs of smart carpets incorporate IR LEDs at varying vision angles and positions. Validation of the prototypes includes laboratory testing and real-world evaluations with the researchers. The assessment encompasses the observation of IR LEDs on the smart shirt and carpets from diverse perspectives, evaluating their light intensity, and assessing their operational synchronization. The findings contribute to the advancement of technology-assisted methodologies in capturing and analyzing interpersonal interactions, particularly in the context of autism research.